Meaning Of Yoga In Ryan Murphy's "Eat Pray Love" Movie(2010): An Individual Psychological Approach - Kurniawati, Devi, Dr.Phil. Dewi Chandraningrum, S.Pd., M.Pd, Titis Setyabudi, S.S. M. Hum (2014)
This Study is about Meaning of Yoga in Eat Pray Love. The problem of this study is how is the meaning of Yoga to the major character reflected in Ryan Murphy's Eat Pray Love movie. The object of the study is Eat Pray Love movie directed by Ryan Murphy. It uses an Individual psychological Approach. This study belongs to qualitative research. There are two types of data source in this method, namely primary and secondary data source. The primary data source is the movie and the movie's script and the secondary data is other material related to the study. Both data are collected and analyzed by descriptive analysis. The result of the study shows the following conclusion, based on the analysis it is clear that this movie reflects about the effort of the major character, Liz Gilbert, who wants to achieve all of her desires. Murphy wants to show the power of ones with her unique way to get something and the meaning of Yoga in her life through Eat Pray Love movie.